The Effect of Using Authentic Materials on Students' Procedural Text Writing Skill At Smas Isen Mulang Palangka Raya - Sriwahyuni, Riza; Perdana, Indra; Karani, Elannari (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2024)
Writing is a skill that requires not only linguistic abilities such as vocabulary and grammar, but also practical knowledge of how to express ideas in written form. Writing also helps us to gain a deeper understanding of something. In the context of teaching procedural text writing, finding appropriate materials for the classroom can be a challenge. This study aims to determine the effect of the use of authentic teaching materials on students' procedural text writing skills at SMAS Isen Mulang Palangka Raya. The method in this research is Pre-Experimental research method, with One-Group Pretest-Posttest Design. The findings of the study show that the use of authentic materials has a positive impact on improving students' writing scores, especially in organization.